Recognizing lifelong learning via credit systems - Strategies and practices of selected European countries - Annen, Silvia [Verfasser]; Eberhardt, Christiane [Verfasser] (My University, 2013)
"In general credit systems are supposed to facilitate transparency, comparability, transferability and mutual recognition of proved learning outcomes and to contribute to a better permeability of the educational system. It is peculiar that within the pan-European initiatives towards the implementation of credit systems the central elements are the awarding of credits and the accumulation of certified learning outcomes on the basis of modular structured units of qualification. Regardless of these central elements the core of a credit system lies within facilitating access and transmission between different learning contexts and shortening the duration of training. Therefore the crucial questions of this paper are if in selected countries already approaches and models exist, which also aim to facilitate transparency, comparability and recognition and on which central elements they are based. Relevant examples, which are implemented respectively discussed, can be found in Germany, Denmark, the Netherlands and Scotland." (Authors' abstract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Europäisches Leistungspunktesystem; Anrechnung von Bildungsleistungen; Auslandsqualifikation; Anerkennung; Verfahren; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Niederlande; Schottland